2019
DOI: 10.2340/00015555-3050
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Vitamin D but not Regulatory T Cells following Ultraviolet B Phototherapy of Patients with Atopic Dermatitis

Abstract: SIGNIFICANCE Vitamin D synthesis is induced by ultraviolet B irradiation of the skin and may have a beneficial effect on the immune system in patients with atopic dermatitis. We measured changes in vitamin D levels and immunological markers in patients with atopic dermatitis receiving ultraviolet B photo therapy. Following ultraviolet B phototherapy, vitamin D levels were increased, as expected, but no changes were found in the immune system. Furthermore, ultraviolet B phototherapy induced equal increases in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(47 reference statements)
0
4
0
1
Order By: Relevance
“…Table S1; for all online suppl. material, see www.karger.com/doi/10.1159/000514308) was determined in biopsies by real-time quantitative polymerase chain reaction (RT-qPCR) performed by AROS Applied Biotechnology A/S (Aarhus, Denmark), as described previously [13]. Expression analysis of RT-qPCR data was performed as described by Pfaffl [5].…”
Section: Methodsmentioning
confidence: 99%
“…Table S1; for all online suppl. material, see www.karger.com/doi/10.1159/000514308) was determined in biopsies by real-time quantitative polymerase chain reaction (RT-qPCR) performed by AROS Applied Biotechnology A/S (Aarhus, Denmark), as described previously [13]. Expression analysis of RT-qPCR data was performed as described by Pfaffl [5].…”
Section: Methodsmentioning
confidence: 99%
“…Another potential mechanism of the protective phototherapy on cardiovascular system includes vitamin D. Phototherapy is known to increase serum concentration of 25(OH)D3 37–39 . Vitamin D deficiency may result in enhanced susceptibility of cardiovascular diseases via pro‐oxidant and pro‐inflammatory mechanisms, and have an influence on endothelial function and arterial thrombogenesis 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attempted to improve bone morphology in animal models or human subjects using UVR [13,28,29,30], although many studies have demonstrated that UVR is effective on increasing the supply of vitamin D [13,28,29,30,31,32,33]. Of these studies, only the report by Guo [30] showed that long-term UVR (12-weeks) improved bone mineral content and bone mineral density in young rats.…”
Section: Discussionmentioning
confidence: 99%